Measuring the Irrigation Requirement of Container-Grown Nursery Plants - Jeff Million; Tom Yeager (EDIS, 2012)
Three factors determine the irrigation requirement for container-grown crops: evapotranspiration, capture factor, and distribution uniformity. This 4-page fact sheet describes how these factors can be measured so that irrigation requirements can be determined in the container nursery. Written by Jeff Million and Tom Yeager, and published by the UF Department of Environmental Horticulture, June 2012.